1983
DOI: 10.1002/cne.902170302
|View full text |Cite
|
Sign up to set email alerts
|

Modifications in the laminar organization of peptide‐like immunoreactivity in the anuran optic tectum following retinal deafferentation

Abstract: Substance P (SP)-, leucine-enkephalin (LENK)-, cholecystokinin octapeptide (CCK8)-, bombesin (BOM)-, and avian pancreatic polypeptide (APP)-like immunoreactivities were analyzed in the optic tectum of Rana pipiens 5-99 days after unilateral eye enucleation, or optic nerve ligation, by means of the peroxidase-antiperoxidase and indirect fluorescence single and double labeling methods. The normal pattern (Kuljis and Karten, '81, '82c) of peptide-like immunoreactivity was observed ipsilaterally to the operation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
1

Year Published

1986
1986
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 26 publications
6
81
1
Order By: Relevance
“…In the frog there is evidence for the existence of neuropeptide-containing ganglion cells as well. Immunocytochemical studies in frog have shown the following: (1) Several specific types of peptidergic fibers are reduced or eliminated from retinal terminal layers of the tectum after enucleation (Kuljis and Karten, 1983), and there can be regeneration of peptide-containing retinofugal axons back into the optic tectum (Kuljis and Karten, 1985a); (2) optic nerve Cb, cerebellum FL&f, fasciculus longitudinalis medialis G, ganglion cell layer GM, nucleus geniculatis lateralis pars dorsalis Hb, nucleus habenularis iLANT-6, immunoreactive LANT-6 Imc, nucleus isthmi pars magnocellularis iNT, immunoreactive neurotensin IP, nucleus interpeduncularis LM, nucleus lentiformis mesencephali LoC, locus coeruleus ME, median eminence N, inner nuclear layer nBOR, nucleus basal optic root nDCP, nucleus dorsalis commissuralae posterioris NHy, nucleus hypophysis nlV', nucleus nervi trochlearis NP, nucleus pretectalis nPM, nucleus profundus mesencephali nS0, nucleus supraopticus nIlI, nucleus nervi oculomototius P, inner plexiform layer PD, peduncularis dorsalis fasciculi prosencephali lateralis PV, peduncularis ventralis fasciculi prosencephali lateralis R, nucleus rotundus SN, substantia nigra TeO, tectum opticum TO, tractus opticus TSC, torus semicircularis TT, tractus tectothalamicus Figure 16. Section through the region of the area preteetalis showing prominent LANT-6-like immunoreactivity on the control sides (arrowhead) but almost total depletion on the experimental sides (arrow) following the degeneration of the ganglion cell axons.…”
Section: Central Projectionsmentioning
confidence: 99%
“…In the frog there is evidence for the existence of neuropeptide-containing ganglion cells as well. Immunocytochemical studies in frog have shown the following: (1) Several specific types of peptidergic fibers are reduced or eliminated from retinal terminal layers of the tectum after enucleation (Kuljis and Karten, 1983), and there can be regeneration of peptide-containing retinofugal axons back into the optic tectum (Kuljis and Karten, 1985a); (2) optic nerve Cb, cerebellum FL&f, fasciculus longitudinalis medialis G, ganglion cell layer GM, nucleus geniculatis lateralis pars dorsalis Hb, nucleus habenularis iLANT-6, immunoreactive LANT-6 Imc, nucleus isthmi pars magnocellularis iNT, immunoreactive neurotensin IP, nucleus interpeduncularis LM, nucleus lentiformis mesencephali LoC, locus coeruleus ME, median eminence N, inner nuclear layer nBOR, nucleus basal optic root nDCP, nucleus dorsalis commissuralae posterioris NHy, nucleus hypophysis nlV', nucleus nervi trochlearis NP, nucleus pretectalis nPM, nucleus profundus mesencephali nS0, nucleus supraopticus nIlI, nucleus nervi oculomototius P, inner plexiform layer PD, peduncularis dorsalis fasciculi prosencephali lateralis PV, peduncularis ventralis fasciculi prosencephali lateralis R, nucleus rotundus SN, substantia nigra TeO, tectum opticum TO, tractus opticus TSC, torus semicircularis TT, tractus tectothalamicus Figure 16. Section through the region of the area preteetalis showing prominent LANT-6-like immunoreactivity on the control sides (arrowhead) but almost total depletion on the experimental sides (arrow) following the degeneration of the ganglion cell axons.…”
Section: Central Projectionsmentioning
confidence: 99%
“…Nevertheless, recent experiments have provided strong evidence in favor of the once seemingly unlikely existence of PLI within RCGs. Retinal ablation is rapidly followed by a drastic reorganization of neuroactive peptide-containing laminae within the retinorecipient neuropil, including the loss of PLI from several laminae (3). Mechanical blockade of axoplasmic flow-by sectioning, ligating, or crushing the optic nerve-results in the buildup of histochemically detectable PLI in the optic nerve as early as 1-2 hr after the procedure (4).…”
mentioning
confidence: 99%
“…Optic nerve lesions cause the degeneration of retinal ganglion cell terminals in the tectum and the disappearance of elements associated with them. 49,60,70 Optic nerve lesions had no significant effect on specific [ 3 H]pirenzepine binding in the tectum (Fig. 7A, B).…”
Section: Effect Of Optic Nerve Lesions On [ 3 H]pirenzepine and [ 3 Hmentioning
confidence: 90%
“…Earlier studies have shown that most retinal fibers in the tectum have degenerated after short-term lesions, but long-term lesions allow for the degeneration of all presynaptic retinal fibers. 49,60,70 Behavioral tests were conducted during the survival period to demonstrate that animals responded only to prey seen through the unlesioned left eye. At the end of the survival period, the frogs were anesthetized, the optic nerve lesion was confirmed and the brain was prepared for autoradiography as described above.…”
Section: Pharmacology Of Muscarinic Binding In the Optic Tectum-autormentioning
confidence: 99%